Th1 and Th2 cytokine profile in patients with early onset periodontitis and their healthy siblings - Jiřina Bártová; Zuzana Krátká-Opatrná; Jarmila Procházková; Otakar Krejsa; Jana Dušková; Lubor Mrklas; Helena Tlaskalová; Božena Cukrowská (Mediators of Inflammation)
Early onset periodontitis (EOP) is a chronic inflammatory periodontal disease with a strong genetic link affecting individuals aged 17 to 25. In the familial studies we tested the hypothesis about the role of Th1 and Th2 cytokines in the pathogenesis of EOP disease. The study involved 6 individuals with EOP disease and their 6 siblings with healthy periodontium. Actinobacillus actinomycetemcomitans (A. a.), a bacterium typical for EOP, was detected in all people studied. Th1 and Th2 cytokine production was measured after in vitro stimulation. Peripheral blood mononuclear cells (PBMC) were isolated and cultivated for 24 h and 7 days with PWM, A. a. or Escherichia coli. The levels of IL–4, IFN-gamma, IgA, IgG and IgM were measured by ELISA methods. After in vitro stimulation of PBMC, a significantly higher production of IL–4 and significantly lower production of IFN-gamma were found in the group of patients compared with their healthy siblings. The increased level of IL–4 in patients was in good agreement with an increased level of IgM after stimulation of lymphocytes with E. coli. These results support Seymour’s hypothesis according to which patients with progressive disease primarily activate Th2 lymphocytes while non-susceptible individuals activate Th1 lymphocytes.